Anamorelin in patients with non-small-cell lung cancer and cachexia (ROMANA 1 and ROMANA 2): results from two randomised, double-blind, phase 3 trials. Issue 4 (April 2016) - Temel, Jennifer S; Abernethy, Amy P; Currow, David C; Friend, John; Duus, Elizabeth M; Yan, Ying; Fearon, Kenneth C
Summary: Background: Patients with advanced cancer frequently experience anorexia and cachexia, which are associated with reduced food intake, altered body composition, and decreased functionality. We assessed anamorelin, a novel ghrelin-receptor agonist, on cachexia in patients with advanced non-small-cell lung cancer and cachexia. Methods: ROMANA 1 and ROMANA 2 were randomised, double-blind, placebo-controlled phase 3 trials done at 93 sites in 19 countries. Patients with inoperable stage III or IV non-small-cell lung cancer and cachexia (defined as ≥5% weight loss within 6 months or body-mass index <20 kg/m 2 ) were randomly assigned 2:1 to anamorelin 100 mg orally once daily or placebo, with a computer-generated randomisation algorithm stratified by geographical region, cancer treatment status, and weight loss over the previous 6 months. Co-primary efficacy endpoints were the median change in lean body mass and handgrip strength over 12 weeks and were measured in all study participants (intention-to-treat population). Both trials are now completed and are registered with ClinicalTrials.gov, numbers NCT01387269 and NCT01387282 . Findings: From July 8, 2011, to Jan 28, 2014, 484 patients were enrolled in ROMANA 1 (323 to anamorelin, 161 to placebo), and from July 14, 2011, to Oct 31, 2013, 495 patients were enrolled in ROMANA 2 (330 to anamorelin, 165 to placebo). Over 12 weeks, lean body mass increased in patients assigned to anamorelin compared with those assigned to placebo in ROMANA 1 (median increase 0·99 kg [95% CI 0·61 to 1·36] vs −0·47 kg [–1·00 to 0·21], p<0·0001) and ROMANA 2 (0·65 kg [0·38 to 0·91] vs −0·98 kg [–1·49 to −0·41], p<0·0001). We noted no difference in handgrip strength in ROMANA 1 (−1·10 kg [–1·69 to −0·40] vs −1·58 kg [–2·99 to −1·14], p=0·15) or ROMANA 2 (−1·49 kg [–2·06 to −0·58] vs −0·95 kg [–1·56 to 0·04], p=0·65). There were no differences in grade 3–4 treatment-related adverse events between study groups; the most common grade 3–4 adverse event was hyperglycaemia, occurring in one (<1%) of 320 patients given anamorelin in ROMANA 1 and in four (1%) of 330 patients given anamorelin in ROMANA 2. Interpretation: Anamorelin significantly increased lean body mass, but not handgrip, strength in patients with advanced non-small-cell lung cancer. Considering the unmet medical need for safe and effective treatments for cachexia, anamorelin might be a treatment option for patients with cancer anorexia and cachexia. Funding: Helsinn Therapeutics.